2021
DOI: 10.1002/ece3.8353
|View full text |Cite
|
Sign up to set email alerts
|

Changes and drivers of zooplankton diversity patterns in the middle reach of Yangtze River floodplain lakes, China

Abstract: Anthropogenic habitat alteration interferes the natural aquatic habitats and the system's hydrodynamics in the Yangtze River floodplain lakes, resulting in a serious decline in freshwater biodiversity. Zooplankton communities possess major position in freshwater ecosystems, which play essential parts in maintaining biological balance of freshwater habitats. Knowledge of processes and mechanisms for affecting variations in abundance, biomass, and diversity of zooplankton is important for maintaining biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 118 publications
(130 reference statements)
11
4
1
Order By: Relevance
“…Significant differences in the diversity of zooplankton were found among the different seasons. The diversity of zooplankton in spring and summer was greater than those in autumn and winter, which was similar to those in studies based on traditional biomonitoring methods (Chen et al, 2020 ; Lu et al, 2021 ; Lv, 2019 ). Such temporal distribution patterns of zooplankton in the Poyang Lake Basin have also been reported by previous microscopy‐based studies (Chen et al, 2020 ; Lu et al, 2021 ; Lv, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Significant differences in the diversity of zooplankton were found among the different seasons. The diversity of zooplankton in spring and summer was greater than those in autumn and winter, which was similar to those in studies based on traditional biomonitoring methods (Chen et al, 2020 ; Lu et al, 2021 ; Lv, 2019 ). Such temporal distribution patterns of zooplankton in the Poyang Lake Basin have also been reported by previous microscopy‐based studies (Chen et al, 2020 ; Lu et al, 2021 ; Lv, 2019 ).…”
Section: Discussionsupporting
confidence: 86%
“…The diversity of zooplankton in spring and summer was greater than those in autumn and winter, which was similar to those in studies based on traditional biomonitoring methods (Chen et al, 2020 ; Lu et al, 2021 ; Lv, 2019 ). Such temporal distribution patterns of zooplankton in the Poyang Lake Basin have also been reported by previous microscopy‐based studies (Chen et al, 2020 ; Lu et al, 2021 ; Lv, 2019 ). The temporal distribution in the relative abundance of zooplankton major groups was also consistent with the plankton ecology group model (PEG model emphasized the role of physical factors, grazing and nutrient limitation for phytoplankton, and the role of food limitation and fish predation for zooplankton; Sommer et al, 2012 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, the regional phytoplankton taxa richness in our wetlands was lower than the 360 phytoplankton species in the Bhoj wetland of India (Bhat et al, 2015), 97 species in of Pantanal wetland of South America (Cardoso et al, 2012), and 200 species in Danube Riverine wetlands of Austria (Chaparro et al, 2018). Similarly, the regional taxon richness of zooplankton in our study was higher than the 32 species reported from the wetland of Opa Reservoir (Adebayo et al, 2021), but lower than the 128 species reported from the Yangtze River floodplain (Lu et al, 2021).…”
Section: Discussioncontrasting
confidence: 63%